2016
DOI: 10.1002/jbm.b.33650
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethyl siloxane based nanocomposites with antibiofilm properties for biomedical applications

Abstract: Polydimethyl siloxane (PDMS) is an excellent implant material for biomedical applications, but often fails as it is prone to microbial colonization which forms biofilms. In the present study CuO, CTAB capped CuO, and ZnO nanoparticles were tested as nanofillers to enhance the antibiofilm property of PDMS against Staphylococcus aureus and Escherichia coli. In general S. aurues (Gram positive and more hydrophobic) favor PDMS surface than glass while E. coli (Gram negative and more hydrophilic) behaves in a rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A wide range of different implant materials are used in orthopedics. Despite the intensive research currently being performed on different technologies for incorporating antimicrobial agents [22][23][24][25][26][27][28][29][30][31][32], only a few studies investigating biofilm formation on different clinically relevant implantation materials have been published [33][34][35][36][37][38]. The dynamic changes associated with biofilm growth [39] make biofilm eradication from clinical materials even more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of different implant materials are used in orthopedics. Despite the intensive research currently being performed on different technologies for incorporating antimicrobial agents [22][23][24][25][26][27][28][29][30][31][32], only a few studies investigating biofilm formation on different clinically relevant implantation materials have been published [33][34][35][36][37][38]. The dynamic changes associated with biofilm growth [39] make biofilm eradication from clinical materials even more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, there are previous published reports where growth of eukaryotic cells on copper surfaces has also been reported. 50 On the other hand the tolerance of heavy metal (Cu) by bacteria is comparatively less (e.g., 1 × 10 −8 M or 0.6355 ppb of copper ion concentration is cytotoxic for Klebsiella aerogenes, a Gram-negative bacteria 51 ). Hence the PDMS_Cu surface can be used as an antibacterial surface for healthcare applications surface while supporting the survival of RAW macrophage and HeLa cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Though in our study we did not use L929 cells, it can be apprehended from the reported data that the tolerance of heavy metal (Cu) ions by eukaryotic cell line is higher. On the one hand, there are previous published reports where growth of eukaryotic cells on copper surfaces has also been reported . On the other hand the tolerance of heavy metal (Cu) by bacteria is comparatively less (e.g., 1 × 10 –8 M or 0.6355 ppb of copper ion concentration is cytotoxic for Klebsiella aerogenes , a Gram-negative bacteria).…”
Section: Resultsmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) as a polymer has low cost and low toxicity and is easy to prepare, which has been used as a matrix material for applications in various scenarios. PDMS is an excellent hydrophobic material, and it has been used as a matrix for the treatment of dirt in water . As an excellent hydrophobic material, Zhang et al (2014) used PDMS coatings to improve the hydrophobicity of MOF-5, HKUST-1, and ZnBT.…”
Section: Introductionmentioning
confidence: 99%